The educational product of professional graduate programs: Proposition from the conceptual, pedagogical and communicational axis (Research, Society and Development, 2024)
In this article we aimed to present the stages we experienced as researchers to understand the theoretical and practical dimension for the elaboration, application and evaluation of an educational product in the context of a master's program, in the professional modality.  To define the educational product, we followed the guidelines contained in the CAPES Teaching Area Document (2019). Thus, we considered that the workshop typology would meet the needs and characteristics of our target audience in a peculiar way. In this way, we idealized an educational product that would provide knowledge to students of the 3rd year of the Technical Course of Informatics Integrated to High School, at the Federal Institute of Santa Catarina, Blumenau Campus, about the existing possibilities for the continuity of the training process at the end of integrated high school. As for the methodological procedure, the present study presents the experience report of a descriptive, documentary and bibliographic research with a qualitative approach. In this way, we have the effective possibility of expanding students' access to knowledge that supports them to continue their training process. This represents significant actions in the lives of many students who seek an EFA institution to expand their opportunities for insertion in the world of work.